Peran Sistem Pembiayaan dalam Peningkatan Mutu dan Penawaran Pendidikan Di Indonesia - Dwi Citra Haryati; Alya Putri Aiska (Universitas Pendidikan Ganesha, 2026)
Education financing plays a strategic role in improving the quality and expanding the offering of educational services in Indonesia. Unequal allocation of funds, particularly between urban and remote areas, remains a major challenge, impacting infrastructure quality, educator competency, and the provision of learning resources. This article aims to analyze how financing systems, whether from the government, community contributions, or internal school management, influence the quality and offering of education, and how collaboration between stakeholders strengthens the effectiveness of financing. The study employed a systematic literature review method, examining 10 relevant articles selected through a process of identification, screening, and thematic analysis. The results indicate that financing managed based on the principles of accountability, transparency, integrity, consistency, effectiveness, and efficiency contributes significantly to improving the quality of educational inputs, processes, and outputs. Furthermore, the approach of financing as an investment in human capital emphasizes the importance of education as a long-term investment in developing skills and national competitiveness. Other findings indicate that collaboration between the government, schools, parents, and the community through school-based management, open communication, and cross-sector partnerships is key to strengthening educational services and shaping student character. In conclusion, the quality and offering of quality education is the result of synergy between good financial management, strengthening human resource investment, and ongoing collaboration from all stakeholders